Crystal chemistry of clinker relicts from aged cementitious materials. (1st October 2014) - Secco, Michele; Peruzzo, Luca; Palasse, Laurie; Artioli, Gilberto; Viani, Alberto; Gualtieri, Alessandro Francesco
<x xml:space="preserve">Abstract</x> Despite the general tendency to consider Portland cement virtually fully hydrated within a few years, the occurrence of non‐reacted clinker phases in cementitious materials that are several decades old is rather common. In this work, the integration of microstructural analysis by scanning electron microscopy and quantitative microchemical and micromineralogical characterization techniques, such as electron microprobe analysis and electron backscatter diffraction, allowed the definition of the crystal‐chemical properties of partially hydrated cement residuals within different types of aged cementitious materials. The results on several clinker relicts show that the calcium silicate phases are transformed systematically and pervasively by hydration reactions, whereas the aluminate and ferrite phases do frequently persist in the anhydrous state. These relict phases may be distinguished through their peculiar chemical, mineralogical and textural features. These observations raise interesting questions concerning the long‐term hydration kinetics of clinker phases and the durability behaviour of cementitious materials in operating conditions.